2017
DOI: 10.1111/ejh.12959
|View full text |Cite
|
Sign up to set email alerts
|

Waldenström′s macroglobulinemia: Two malignant clones in a monoclonal disease? Molecular background and clinical reflection

Abstract: Waldenström′s macroglobulinemia (WM) is a complex disease characterized by apparent morphological heterogeneity within the malignant clonal cells representing a continuum of small lymphocytes, plasmacytoid lymphocytes, and plasma cells. At the molecular level, the neoplastic B cell-derived clone has undergone somatic hypermutation, but not isotype switching, and retains the capability of plasmacytic differentia- | REGULATION OF B-CELL DEVELOPMENT: WHERE IS THE MISTAKE?Tumor cells of Waldenström′s macroglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
(126 reference statements)
1
9
0
Order By: Relevance
“…Indeed, the transcriptional factor LEF1 was under expressed in WM and IgM MGUS vs. CTRLs as well as vs. CLL B-cells [5,15,41,42]. Moreover, LEF1 was over expressed in immature normal B-cells compared to mature normal B-cells [42]. In line with these studies, we showed that LEF1 was down regulated in WM and IgM MGUS compared to CTRLs B-cells.…”
Section: Adherens Junctions and Wnt Signaling Pathwaysupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, the transcriptional factor LEF1 was under expressed in WM and IgM MGUS vs. CTRLs as well as vs. CLL B-cells [5,15,41,42]. Moreover, LEF1 was over expressed in immature normal B-cells compared to mature normal B-cells [42]. In line with these studies, we showed that LEF1 was down regulated in WM and IgM MGUS compared to CTRLs B-cells.…”
Section: Adherens Junctions and Wnt Signaling Pathwaysupporting
confidence: 84%
“…Several studies have demonstrated the deregulation of genes associated with the Wnt pathway in B-cell disorders and MM. Indeed, the transcriptional factor LEF1 was under expressed in WM and IgM MGUS vs. CTRLs as well as vs. CLL B-cells [5,15,41,42]. Moreover, LEF1 was over expressed in immature normal B-cells compared to mature normal B-cells [42].…”
Section: Adherens Junctions and Wnt Signaling Pathwaymentioning
confidence: 98%
“…somatic hypermutation or ongoing IGH mutations, leading to two partially-different independent tumoral clones [16]. MYD88-L265P mutation has been considered a driver mutation in the development of WM, and in most cases of MGUS that evolve into WM [4].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, most cases (82%) were of non-GC phenotype, like in our series, where all 7 DLBCL cases displayed a non-GC phenotype. It has been classically considered that the clonal lymphoplasmacytic cell phenotype in WM corresponds to the late stage of Bcell differentiation and is derived from IgM-producing memory B cells that have undergone somatic hypermutation, but not isotype switching [16]. In general, it is worth mentioning that most ABC-DLBCL has not undergone class switching, and ABC-DLBCL express IgM more frequently than GCB-DLBCL [23,24].…”
Section: Plos Onementioning
confidence: 99%
“…Combination therapies have a synergistic activity that may provide a vital overlap to eradicate the entire WM clone [20]. The preferred frontline treatment options for WM can be broadly classified as rituximab-alkylator combination therapy, proteasome inhibitor-based therapy, and Bruton's tyrosine kinase (BTK) inhibitor-based therapy.…”
Section: Rituximab As a Monotherapymentioning
confidence: 99%